2005
DOI: 10.1016/j.ydbio.2005.08.029
|View full text |Cite
|
Sign up to set email alerts
|

The Iroquois homeobox gene, Irx5, is required for retinal cone bipolar cell development

Abstract: In the mouse retina, at least ten distinct types of bipolar interneurons are involved in the transmission of visual signals from photoreceptors to ganglion cells. How bipolar interneuron diversity is generated during retinal development is poorly understood. Here, we show that Irx5, a member of the Iroquois homeobox gene family, is expressed in developing bipolar cells starting at postnatal day 5 and is localized to a subset of cone bipolar cells in the mature mouse retina. In Irx5-deficient mice, defects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
96
2

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 94 publications
(100 citation statements)
references
References 50 publications
1
96
2
Order By: Relevance
“…In addition, ERGs of Vsx1-deficient mice showed a reduced b-wave, a measure of bipolar cell activity, and OFF but not ON RGCs fired on average fewer spikes in response to steps in light intensity compared with their wild-type counterparts (Chow et al, 2004;Ohtoshi et al, 2004). In contrast, preliminary studies revealed no specific b-wave defects in ERGs from Irx5-deficient mice (Cheng et al, 2005). These findings argued that Vsx1 and Irx5 regulate the differentiation of OFF cone bipolar cells and suggested their possible importance for retinal function.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations
“…In addition, ERGs of Vsx1-deficient mice showed a reduced b-wave, a measure of bipolar cell activity, and OFF but not ON RGCs fired on average fewer spikes in response to steps in light intensity compared with their wild-type counterparts (Chow et al, 2004;Ohtoshi et al, 2004). In contrast, preliminary studies revealed no specific b-wave defects in ERGs from Irx5-deficient mice (Cheng et al, 2005). These findings argued that Vsx1 and Irx5 regulate the differentiation of OFF cone bipolar cells and suggested their possible importance for retinal function.…”
Section: Introductionmentioning
confidence: 82%
“…Mice that were heterozygous or null for Vsx1 and Irx5 were bred from single gene knock-out mice of Vsx1 (Chow et al, 2004) and Irx5 (Cheng et al, 2005) and genotyped using the following primer sets: Vsx1 genotyping: common 5Ј primer, TTC TAG GCT GTC TAG GTC TC; wild-type 3Ј primer, TGA TGG CAA AGC TTC GAA GG; mutant 3Ј primer, TTG CCT TTA CTG ACC ATG CG; Irx5 genotyping: wild-type 5Ј primer, ACC GCT TCC TCG TGC TTT AC; mutant 5Ј primer, GCC ACC CAA AAG ACT GAA ACC; common 3Ј primer, TAA ACC TAT CTT CGC AAT CC. These mice were in a mixed 129/Sv and CD1 background.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the architecture and major class of neurons as well as the neurogenesis events in the fish eye are reminiscent of the progression of the morphogenetic furrow in the Drosophila eye. We previously demonstrated that mouse Irx5 plays a unique role in the differentiation of specific bipolar neurons (Cheng et al, 2005). Furthermore, we have showed that, in the zebrafish, irx1a (Cheng et al, 2001;Wang et al, 2001;Itoh et al, 2002;Dildrop and Rü ther, 2004;Feijoo et al, 2004) plays an early function in retinogenesis (Cheng et al, 2006) and serotonergic neuron differentiation (Cheng et al, 2007).…”
Section: Introductionmentioning
confidence: 92%